Fe-N Decorated Hybrids of CNTs Grown on Hierarchically Porous Carbon for High-Performance Oxygen Reduction - Liang, Ji; Zhou, Rui Feng; Chen, Xue Min; Tang, You Hong; Qiao, Shi Zhang (Advanced materials (Weinheim), 2014)
An Fe–N‐decorated hybrid material of carbon nanotubes (CNTs) grown in situ from porous carbon microblocks is designed and constructed. This material successfully combines the desirable merits for oxygen reduction reaction (ORR), such as highly active Fe–N species, good conductivity, large pore size, and sufficient surface area. These structural advantages give this low‐priced material an outstanding catalytic performance for ORR closely comparable with Pt/C of the same quantity.